Recent progress and development trend of femtosecond pulsed-laser for single event effects assessment - AN Heng; LI Detian; YANG Shengsheng; WANG Yi; CAO Zhou; WEN Xuan; WANG Jun; ZHANG Chenguang; YIN Hong (He jishu, 2021)
The current status and technical development trend of single event effect (SEE) induced by two-photon absorption (TPA) of femtosecond pulsed laser at home and abroad are reviewed. Effect of nonlinear optical phenomena, such as TPA, free carrier absorption and refraction, on carrier density distributions induced by TPA are analyzed. Based on the carrier density distribution model, the method of determining the sensitive depth of device based on Z scan is discussed. The application requirements and prospects of femtosecond pulsed laser in the in-depth study of SEE mechanism, screening of space mission devices and radiation hardness evaluation of electronic equipment, etc., are summarized, providing suggestions and opinions for further expanding the application of femtosecond pulsed laser single-particle effect test technology in radiation resistance evaluation of space equipment and satellite electronic equipment.